Influence of Underpinning Pile Drilling Construction on the Bearing Behavior of Existing Loaded Foundation Piles: Case Study - Hua-feng Shan; Tang-dai Xia; Feng Yu; Hai-bing Tao; Shao-heng He (Advances in Civil Engineering)
The mechanism of drilling borehole and its influence on the bearing behavior of existing foundation piles are unclear, hindering the application of excavation techniques. This paper proposes a new excavation scheme for high-rise buildings in downtown and develops theoretical formulas to calculate the skin friction and end resistance of existing foundation piles affected by adjacent borehole drilling for installing underpinning piles. These underpinning piles are installed and connected with the existing pile by the head cap before excavation. In a case study, the parameter analysis was then performed to understand the effect of underpinning construction on the bearing behavior of existing foundation piles in terms of skin friction and end resistance. The results show that borehole diameter, depth of drilling borehole, distance between the existing foundation pile and drilling borehole, and number of boreholes have a negligible influence on the end resistance of existing foundation piles. The effect of drilling parameters on the skin friction of existing foundation pile, as well as the influence extent, varies for different parameters. The depth of drilling borehole and the number of boreholes have significant influence and thus should be considered in real engineering design while the borehole diameter and the pile-pile distance have a negligible effect. The proposed new excavation technique could be potentially adopted for real engineering design of underneath excavation projects for high-rise buildings in downtown.